Regional Cohesion and Competition in the Age of Globilization - Kōno, Hirotada; Nijkamp, Peter; Poot, Jacques (Cheltenham, England ; Northampton, MA, USA : Edward Elgar, 1999)
This book discusses issues including the impact and implications of European expansion as well as developments in the Asia-Pacific region. This work also examines the driving forces, backgrounds, obstacles and opportunities for regions to become powerful global players.
Includes bibliographical references and index.
rpm 08/09/2016
Loans
Keywords: Competition, International; Competition; International economic integration; Regionalism; Regional economics; International trade